Modulation of redox homeostasis by Lamiaceae herbs in seminal vesicles of Lumbricus terrestris - Vattem, Dhiraj Anil; DeLeon, Robert Corey (Free Radicals and Antioxidants)
Background/Aims: Health benefits of Lamiaceae herbs are attributed to the presence of antioxidant phytochemicals. However, mechanism of in vivo functionality is not very well understood. We deter- mined the in vivo effect of dietary Lamiaceae herbs on modulating redox-nitric oxide (NO) homeostasis and sperm quality in oxidation prone environment of seminal vesicles in Lumbricus terrestris. Methods: Animals fed ad libitum on Lumbricus growth medium supplemented with 0% (control), 0.1% or 0.5% (w/v) of different herbs. The seminal vesicles of the animal were dissected out on day 2 and day 6, and gently disrupted. Levels of malondialdehyde (MDA), DNA fragmentation (DNAF), glutathione (GSH), nitrates/nitrites (NOx), superoxide dismutase (SOD), catalase (CAT) were determined using standard assays. Sperm maturity and deformation (DFO) was quantified microscopically. Results: Overall, the herb treatments decreased MDA levels by (60e90%), increased SOD activity (15e50%), and decreased DNAF (6e11%). Treatments with basil and oregano at 0.1% (w/v) were most effective. Conclusion: Our suggests that phytochemicals from Lamiaceae herbs modulate redox stress response, and protect against oxidative stress in seminal vesicles.
Keywords: Lamiaceae herbs; Oxidative stress; Antioxidant activity; Redox modulation; Lumbricus terrestris